Penerapan Tata Kelola Syariah Lembaga Keuangan Islam (Studi Kasus Pada PT. BPRS Jabal Nur Surabaya) - Fachruddin ‘Aabid; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
This research aims to analyze the implementation process of good sharia governance (GSG) in order to ensure sharia compliance. Sharia governance is a qualitative disclosure that includes arrangements, systems, and control to ensure sharia compliance. The method using descriptive qualitative approach with case study strategy at PT. Bank Pembiayaan Rakyat Syariah (BPRS) Jabal Nur Surabaya. Data collected by in depth interview and documentation. Validation techniques using source and technic triangulation. Analysis techniques using Miles and Huberman’s.Result of this research is based on seven patterns from the sharia governance process which represents the instrumental function of the sharia supervisory board as part of the internal governance structure of corporate governance in Islamic Financial Institutions. Based on the analysis that has been conducted by researchers, PT. Bank Pembiayaan Rakyat Syariah Jabal Nur has been quite obedient in fulfillment guarantee of sharia compliance based on the implementation process of good sharia governance.